Le GN sans déterminant en « dialecte visuel » de l’allemand - Odile Schneider-Mizony (Corela)
Some contemporary German-speaking authors exploit the discrepancy between the expected presence of the nominal group determinant (Gn) in German and the absence of an actualizer to code a German-Turkish variety, designated by the term Kiez, which metonymically means "language of the neighbourhoods". An example of this is the ritual threat "ich mach dich messer", which could be translated literally as: "I'll make you a knife", which pragmatically corresponds to a meaning such as "you're going to have to deal with my knife". The absence of any determinant for the noun “Messer” creates an unusual language for the German-speaking reader. The contribution analyses the achievements and effects of two contemporary German-Turkish authors: Feridun Zaimoglu in Kanak Sprak, written in this "language of the scoundrels", and Emine Sevgi Özdamar in the title set Mutterzunge, "Language of the mother".